2017
DOI: 10.1055/s-0037-1599111
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental Assessment of Pediatric Dysphagia

Abstract: Speech-language pathologists (SLPs) have fulfilled primary roles in the evaluation and management of children with feeding/swallowing disorders for more than five decades. The increased incidence and prevalence of newborns, infants, and children with feeding and swallowing disorders has resulted in increased use of instrumental swallowing evaluations. The videofluoroscopic swallow study and fiberoptic endoscopic evaluation of swallowing are the two most commonly used swallowing assessments by SLPs, with ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 49 publications
1
35
0
6
Order By: Relevance
“…Primary goals include identifying anatomy, oropharyngeal swallow pathophysiology, the presence and source of laryngeal penetration/ aspiration, effects of behavior, and/or sensory changes on swallowing physiology. [92][93][94] Information from instrumental exams is used to identify specific therapeutic targets for improving swallow function.…”
Section: Goals Of Instrumental Evaluationsmentioning
confidence: 99%
“…Primary goals include identifying anatomy, oropharyngeal swallow pathophysiology, the presence and source of laryngeal penetration/ aspiration, effects of behavior, and/or sensory changes on swallowing physiology. [92][93][94] Information from instrumental exams is used to identify specific therapeutic targets for improving swallow function.…”
Section: Goals Of Instrumental Evaluationsmentioning
confidence: 99%
“…Obrázok 5: Aspirácia, kontrastná látka preniká pod úroveň hlasiviek Dĺžka vyšetrenia: VFSS u detí priemerne trvá od 1,0-8,12 minút (závisí od veku dieťaťa a jeho celkového zdravotného stavu). Novšie štúdie hovoria o priemere medzi 1,58-2,5 minúty (Arvedson, Lefton-Greif, 2017, Henderson et al, 2016. Trvanie je ovplyvnené viacerými faktormi vrátane veku dieťaťa, kvality jeho porúch prehĺtania (napr.…”
Section: Obrázok 4: Penetrácia Kontrastná Látka Konturuje Hornú Plocunclassified
“…Porovnanie oboch najčastejšie používaných objektívnych zobrazovacích metód vyšetrenia aktu prehĺtania u detí uvádzame v tabuľke č. 5 tak, ako ich uvádza Arvedson (Arvedson, Lefton-Greif, 2017…”
Section: Výhody a Limity Vfss A Feesunclassified
“…The reader is referred, however, to the article in this issue by Arvedson and Lefton-Grief for information on the multiple instrumental assessments available for identifying swallowing and feeding problems, some of which arise from gastrointestinal, metabolic, cardiac, respiratory, and other health issues that frequently occur along with DD. 23 Published Assessments Clinical assessments of pediatric feeding fall into the following categories: observational, criterion referenced, standardized, and interview based. A systematic review of noninstrumental swallowing and feeding assessments for children was reported by Heckathorn et al in 2016.…”
Section: Assessment Approachesmentioning
confidence: 99%